Lack of association between NR3C1 polymorphism and glucocorticoid resistance in Chinese patients with immune thrombocytopenia. (March 2014) - Xuan, Min; Li, Huiyuan; Fu, Rongfeng; Yang, Yanhui; Zhang, Donglei; Zhang, Xian; Yang, Renchi
Abstract Resistance to glucocorticoids (GCs) is a tricky problem in therapy for immune thrombocytopenia (ITP). As GCs exert their effects through glucocorticoid receptor (GR), being a GR gene, NR3C1 is thought to connect with individual differences in GC responsiveness during GCs treatments. We analyzed the frequency of three novel single nucleotide polymorphisms (SNPs) of NR3C1 in ITP patients and evaluated the role of these genetic variants in GCs therapy. Four hundred and seventy-three patients with ITP and 160 healthy controls were recruited. Patients were allocated into GCs-responsive (n = 358) and -non-responsive group (n = 115). All subjects of the three groups were genotyped by the PCR-RFLP (restriction fragment length polymorphism) method for the BclI, N363S and ER22/23EK polymorphisms. Assess the statistical differences of genotypes between ITP and controls, and those between GCs- responsive and non-responsive groups. In healthy controls, BclI-GG/GC/CC occurred with 0.581/0.35/0.069 frequency. In ITP patients, BclI-GG/GC/CC was found with 0.617/0.353/0.03 frequency. There was no statistically differences between ITP and controls (p = 0.070). In GCs-responsive and -non-responsive group, BclI-GG, GC, CC occurred with frequencies of 0.628/0.352/0.02 and 0.583/0.357/0.061, respectively. No correlations in the variants of BclI was found between the GCs-responsive and -non-responsive group (p = 0.086). Neither N363S nor ER22/23EK polymorphism was observed in all 636 participants. The BclI polymorphism is not related to the response of GCs in patients with ITP. Furthermore, we did not observe N363S and ER22/23EK polymorphism in Chinese Han population.